Modernizing Tax Administration A Key to Increasing Tax Revenue in Algeria from 2019 to 2023 - hadjar, mabrouka (Journal of Research in Finance and Accounting, 2024)
This study aims to highlight the role of modernizing the tax administration in enhancing tax collection in Algeria during the period 2019-2023. The results indicate that the improvements made to the tax administration in Algeria had a positive impact on increasing tax revenues, with petroleum taxation clearly dominating total revenues. Additionally, there was a significant improvement in the amounts recovered through tax audits, particularly due to the enhanced capability for electronic auditing of taxpayers' accounts. Among the key recommendations are the broader implementation of an electronic payment system and increasing awareness of the importance of modern technology for both taxpayers and tax administration employees.